Chromite Mineralization in the Sopcheozero Deposit (Monchegorsk Layered Intrusion, Fennoscandian Shield) - Artem V. Mokrushin; Valery F. Smol’kin (Minerals, 2021)
In 1990, the Sopcheozero Cr deposit was discovered in the Monchegorsk Paleoproterozoic layered mafic-ultramafic layered intrusion (Monchepluton). This stratiform early-magmatic deposit occurs in the middle part of the Dunite Block, which is a member of the Monchepluton layered series. The Cr2O3 average-weighted content in ordinary and rich ores of the deposit is 16.65 and 38.76 wt.%, respectively, at gradually changing concentrations within the rich, ordinary and poor ore types and ore body in general. The ores of the Sopcheozero deposit, having a ratio of Cr2O3/FeOtotal = 0.9–1.7, can serve as raw materials for the refractory and chemical industries. The ore Cr-spinel (magnochromite and magnoalumochromite) is associated with highly magnesian olivine (96–98 Fo) rich in Ni (0.4–1.1 wt.%). It confirms a low S content in the melt and complies with the low oxygen fugacity. The coexisting Cr-spinel-olivine pairs crystallized at temperatures from 1258 to 1163 °C, with accessory Cr-spinel crystallizing at relatively low, while ore Cr-spinel at higher temperatures. The host rock and ore distinguish with widespread plastic deformations of olivine at the postcrystallization phase under conditions of high temperature (above 400 °C) and pressure (5 kbar). At the post magmatic Svecofennian stage (1.84 Ga), the deposit, jointly with the Monchepluton, was subject to diverse tectonic deformations.